AB0291B A COMPARISON OF THE JOINTS ULTRASONOGRAPHY IN THE PATIENTS WITH RHEUMATOID ARTHRITIS TREATED BY BIOLOGICAL AGENTS AND THE CORRESPONDING SYNOVIAL HISTOLOGICAL FINDINGS. (June 2019) - Abe, Asami; Ishikawa, Hajime; Wakaki, Kunihiko
Abstract : Background: In the treatment of Rheumatoid arthritis (RA), early diagnosis and early treatment with tight control have become increasingly important with the advent of biological therapy. Ultrasonography (US) of the various joints enables the real-time evaluation of synovial hypertrophy, effusion and bone erosion, Power Doppler (PD) ultrasound is able to identify both subclinical synovitis and early erosive disease. Objectives: The objectives of this study were to investigate whether the image of US at the operated joint reflect synovium histological findings or clinical indicators, and to compare the results in the patient treated by non-biological agent (NonBio) and biological agent (Bio) Methods: RA related orthopaedic surgery was performed at 1287 joints including 17 shoulders, 160 knees, 96 elbows, 378 wrists, 364 fingers, 38 ankles and 234 toes during the period between January 2011 and December 2018 at our rheumatic center. Preoperatively, ultrasound evaluations were performed and grade of PD signal was determined at the part with the highest signal. PD signal consists 4 grades from grade 0 to 3. The operations were performed within one week after the ultrasound evaluations. Rooney score of the synovium histology, DAS28-ESR(4), MMP-3, CRP were investigated. Rooney score represents the histologic features in the synovium of RA. It includes 6 features i.e. synoviocytes hyperplasia, fibrosis, proliferating blood vessels, perivascular infiltrates of lymphocytes, focal aggregates of lymphocytes, diffuse infiltrates of lymphocytes. They were scored separately on a scale of 1-10.The treatments that the patients received included: biological agents (Bio) (n=389 30%), etanercept (ETN) (n= 102), tocilizumab (TCZ) (n=105), infliximab (IFX) (n=29), adalimumab (ADA) (n=28), certlizumab pegol (CZP) (n=12), golimumab (GLM) (n=56), and abatacept (ABT) (n=55), tofacitinib (TOF) (n=2). Results: PD signal (0.97±0.88), DAS28 (3.23±1.13), CRP(0.5±1.25 mg/dL), MMP-3 (119.0±119.0 ng/mL) and Rooney score (23.5±7.7) in the patients treated with Bio were significantly lower than those (1.39±0.95, 3.66±1.07, 0.78±1.37 mg/dL, 146.3±150.0ng/dL, 28.5±9.26) in the patients treated with NonBio. Rooney score fibrosis (9.57±1.44) in patients treated with Bio was significantly higher than those (8.64±2.48) in patients treated by NonBio. Rooney score, synoviocyte hyperplasia (1.16±1.26) and three items of lymphocyte (1.59±2.91, 1.68±2.54, 1.11±2.20) in patients treated with Bio were lower than those (1.72±1.30, 3.79±3.56, 3.73±3.53, 2.40±2.98) in patients treated with NonBio. TCZ, ADA, ABT and IFX had some significant differences for Rooney score and Rooney item score between the patients treated with NonBio. Conclusion: The activity of RA synovitis at operated site was suppressed in patients treated with Bio. There were some differences in clinical data, histological score, PD signal and DAS28 among Bio. Disclosure of Interests: None declared